Guía de gestión de la calidad en el proceso de elaboración de magistrales estériles con base en la estructura de alto nivel. (2020)
This paper presents a quality management guide for the elaboration process of compounding sterile preparations based on the high level structure and the minimum requirements of quality assurance and control for the elaboration process, where it is important to take charge and certify the quality, since this process is focused on patient safety and prevention of medication errors. The correspondence of the requirements to the high-level structure is identified as a useful tool for the harmonization of management systems.